INOVASI PEMBELAJARAN SAINTIFIK DENGAN SNOWBALL THROWING DALAM PROSES MENANYA TERHADAP HASIL BELAJAR SISWA - I Nyoman Jampel; I Wayan Widiana; Made Yeni Juliantari (Universitas Pendidikan Ganesha, 2017)
This research is aimed at determine the differences students learning outcome between of students applying scientific approach in process of questioning assisted by Snowball Throwing and students applying conventional learning. This research is a quasi experimental which used non equivalent post-test only control group design. The population were 3rd grade Of Elementary School student in school piloting of Curriculum 2013, Buleleng District with the number of the student were 358 students, through random sampling technique. The data of students’ learning outcomes were collected using regular multiple choice test and essay test. The data were analyzed by using descriptive statistics namely modus, media, mean and inferential statistic, namely t-test. The result of t-test analysis that thitung is greater than ttabel, 2,7327 > 1,9965 with 66 df. It can be concluded that scientific approach in process of questioning assisted by Snowball Throwing gave a significant learning outcomes of 3rd grade elementary school.